In-silico guided design, synthesis and bio-evaluation of potential chemotherapeutic agents against malaria, cancer and disease-causing pathogens - October, Natasha (University of Pretoria, 2022)
Thesis (PhD (Chemistry))--University of Pretoria, 2022.